Combined effect of artificial cervical disc replacement and facet tropism on the index-level facet joints: a finite element study - Jing Li; Yuxiao Deng; Junqi Zhang; Beiyu Wang; Kangkang Huang; Hao Liu; Xin Rong (BMC Musculoskeletal Disorders)
Abstract Background Artificial Cervical Disc Replacement (ACDR) is an effective treatment for cervical degenerative disc diseases. However, clinical information regarding the facet joint alterations after ACDR was limited. Facet tropism is common in the sub-axial cervical spine. Our previous research indicated that facet tropism could lead to increased pressure on the cervical facet joints. This study aimed to assess the impact of facet tropism on the facet contact force and facet capsule stress after ACDR. Methods A C2–T1 cervical finite element model was constructed from computed tomography (CT) scans of a 28-year-old male volunteer. Symmetrical, moderate asymmetrical (7 degrees tropism), and severe asymmetrical (14 degrees tropism) models were created at the C5/C6 level by altering the facet orientation at the C5-C6 level. The C5/C6 ACDR was simulated in the intact, moderate asymmetrical and severe asymmetrical models. A 75-N follower load with 1.0-Nm moments was applied to the top of C2 vertebra in the models to simulate flexion, extension, lateral bending, and axial rotation with the T1 vertebra fixed. The range of motions (ROMs) under all moments, facet contact forces (FCFs) and facet capsule strains were tested. Results In the asymmetrical model, the right FCFs considerably increased under flexion, extension, right bending, left rotation, especially under right bending the right sided FCF of the severe asymmetrical model was about 5.44 times of the neutral position, and 3.14 times of the symmetrical model. and concentrated on the cephalad part of the facets. The facet capsule stresses on both sides remarkably increased under extension, lateral bending and right rotation. In the moderate and severe asymmetrical models, the capsule strain was greater on both sides of each position than in the symmetric model. Conclusions The face tropism increased facet contact force and facet capsule strain after ACDR, especially under extension, lateral bending, and rotation, and also could result in abnormal stress distribution on the facet joint surface and facet joint capsule. The results suggest that face tropism might be a risk factor for post-operative facet joint degeneration progression after ACDR. Facet tropism may be noteworthy when ACDR is considered as a surgical option.